The Existence Of The University Of Muhammadiyah Malang Library During The Covid-19 Pandemic - Dian Puspitasari; Moh Zawawi (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2021)
The Covid-19 virus has caused a pandemic in Indonesia in 2020. This virus is classified as an infectious disease that results in policies such as physical distancing, social restrictions both small and large scale and lockdown. The impact of the Covid-19 virus has been felt in various sectors, including the college sector under which there are library units. The college library as an information center, of course, will provide information services to meet the needs of academic community. UPT UMM Library is one of the universities that still exists despite the Covid-19 pandemic. The purpose in this writing analyzes how the existence of UPT UMM Library during the pandemic.Â The study method used by descriptive study type with qualitative approach and data analysis technique using descriptive qualitative analysis model owned by John W Cresswell. Innovations made by UPT UMM Library during the Covid-19 pandemic to remain in existence, namely to innovate library services including creating myUMM Library, changing the concept of information literacy services into digital (online) and more actively providing library services through social media. In addition, librarians during the Covid-19 pandemic can still exist and develop by attending various online seminars and actively writing various scientific works to gain several champions.